2019
DOI: 10.1111/1759-7714.13023
|View full text |Cite
|
Sign up to set email alerts
|

EGFR exon 21 L858R as an acquired resistance mechanism to nivolumab in a lung cancer patient originally driver gene‐negative

Abstract: The use of immune checkpoint inhibitors targeting PD‐1 and PD‐L1 in advanced non‐small cell lung cancer (NSCLC) has been one of the most significant improvements in recent years. However the resistance mechanisms of immune checkpoint inhibitors require further investigation. Herein we attempted to determine the possible resistance mechanism of nivolumab in a male smoker with advanced adenosquamous carcinoma. After experiencing disease progression on systematic chemotherapy, he was administered nivolumab as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…56 Xia et al described an activating EGFR receptor mutation as an acquired resistance mechanism to the PD-1 antibody nivolumab in a lung cancer patient. 57 These data underline the rationale to combine immune checkpoint inhibitors with other targeted therapies such as bispecific T-cell engagers to evade resistance mechanisms and enhance the therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…56 Xia et al described an activating EGFR receptor mutation as an acquired resistance mechanism to the PD-1 antibody nivolumab in a lung cancer patient. 57 These data underline the rationale to combine immune checkpoint inhibitors with other targeted therapies such as bispecific T-cell engagers to evade resistance mechanisms and enhance the therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the PD-L1 and STAT3 inhibitors have an obvious therapeutic effect on LAD cell lines; and the EGFR mutation subtypes might influence the therapeutic efficacy. One case report has found that the L858R mutation is an acquired resistance mutation to nivolumab (PD-L1 inhibitor) [29], and patients with high PD-L1 expression may exhibit a poor response to EGFR-TKI. In addition, it has reported that the JAK/STAT3 pathway plays an important role in cancer proliferation and invasion, which could promote cancer aggression through inflammation or immunosuppression [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy of two immunotherapy failure patients also showed a sharply decrease of PD-L1 expression after immunotherapy ( 178 ). Acquired EGFR exon 21 L858R has been observed in a nivolumab resistant patient, which may also be a possible mechanism of secondary ICI resistance ( 179 ) ( Figure 2 ).…”
Section: Adverse Effects and Drug Resistance In Immunotherapymentioning
confidence: 99%